2007
DOI: 10.1111/j.1460-9592.2007.02211.x
|View full text |Cite
|
Sign up to set email alerts
|

Postal survey of training in pediatric cardiac anesthesia in the United Kingdom1

Abstract: They would recommend the same experience for others but this is unlikely to happen within the current constraints of specialist registrar training. Therefore, further training in a fellowship program in the UK or abroad is likely to be necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 6 publications
2
12
0
Order By: Relevance
“…White and Murphy conducted a survey aiming on proposing recommendations for training in pediatric cardiac anesthesia in the United Kingdom. The postal survey of British consultant pediatric cardiac anesthetists revealed that the respondents preferred 12 months of training (during the registrarship in anesthesia) in general pediatric anesthesia and 6 months in each of pediatric cardiac anesthesia, pediatric intensive care, adult cardiac anesthesia, and at least 100 pediatric cardiac cases under supervision . Even in the United States there are currently no formal training guidelines or a dedicated certification processes for pediatric cardiac anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…White and Murphy conducted a survey aiming on proposing recommendations for training in pediatric cardiac anesthesia in the United Kingdom. The postal survey of British consultant pediatric cardiac anesthetists revealed that the respondents preferred 12 months of training (during the registrarship in anesthesia) in general pediatric anesthesia and 6 months in each of pediatric cardiac anesthesia, pediatric intensive care, adult cardiac anesthesia, and at least 100 pediatric cardiac cases under supervision . Even in the United States there are currently no formal training guidelines or a dedicated certification processes for pediatric cardiac anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…This has led to formal recommendations by the Congenital Cardiac Anesthesiologists Society (CCAS) . While this advice is aimed at those practicing in North America, it is broadly in agreement with surveys on this subject from other high‐income countries: in essence 1 to 2 years of specialist training, in addition to basic anesthesia training, encompassing pediatric anesthesia, pediatric cardiac anesthesia, and pediatric intensive care, with the aim of acquiring specific competencies and knowledge. Subsequent to fellowship training, newly appointed specialists should expect a period of formal or informal mentorship.…”
mentioning
confidence: 89%
“…In summary, British anesthetists measured a decrease in trainee case loads, and started a discussion about the required changes in training and assessment to counterbalance the lack of practice. Recommendations include 'semi-solo' sessions, more simulator training, new standards for training set by the Royal College of Anaesthetists and rationalized working time concepts [5][6][7].…”
Section: The Situation In the Ukmentioning
confidence: 99%